Analisa Tingkat Keandalan Sistem Gardu Induk 13,8 KV 6DN Minas PT.Chevron Pacific Indonesia Dengan Metode Section Technique - Prima Prima; Dian Yayan Sukma; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Analysis level reliability of this study using methods the section technique. Objectives to be presented in this study provide information about reliability of the substation 6DN PT.Chevron Pacific Indonesia. By dividing the distribution network based methods of calculating level of reliability section technique, which impacts the perceived failure of the same component if the occurrence of the disorders that cause system outages. Step by step execution of this study include collecting data, performing calculations failure parameter, calculating the reliability index SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interuption Frequency Index). The calculating result obtained by using method section technique SAIFI = 2.272817955 time/year and SAIDI = 1.859914796 hour/year. With existing standard in Indonesia as SPLN 68-2 1986 has values SAIFI (System Average Frequency Duration Index) is 3.2 time/year and SAIDI (System Average Interruption Duration Index) is 21 hour/year, the index reliability of the distribution system substation 6DN still in the category reliable. With an international standards such as IEEE Std. 1366-2000 SAIDI reliability index value of the distribution system substation 6DN smaller than the value of SAIDI IEEE Std.1366-2000, for the value of reliability index SAIFI substation 6DN larger than value index SAIFI IEEE Std. 1366-2000.Keywords : Section technique, reliability, system distribution